O Instituto Federal de Sergipe : Campus Itabaiana e suas contribuições para o desenvolvimento local - Boia, Lucila da Silva (2023)
Education plays a crucial role in the acquisition of knowledge and technical improvement of the individual, generating qualified labor. In the meantime, the main objective of this work is to analyze the contributions of the Federal Institute of Sergipe in the municipality of Itabaiana, highlighting the relevance of Professional and Technological Education (EPT) for the formation of human capital and local development. For this, a bibliographical study on the Theory of Human Capital was used, correlating it to economic development. Then, a documentary investigation was carried out on the historical evolution and expansion of the Federal Education Network, also presenting a panoramic view of the performance of the Federal Institute of Sergipe through internal data referring to the year 2021. A theoretical discussion on local development and its relationship with the EPT was presented, as well as the socioeconomic dynamics of the municipalities of the Microregion of Agreste de Itabaiana, specifically of this city. Furthermore, a study was carried out on the implementation of the IFS in Itabaiana and its performance in the dimensions of teaching, research and extension. The method approached was the inductive one, the result of a positivist and empiricist perspective with a descriptive research type. As for the approach, it was investigated in a qualitative and quantitative way. Regarding the methodological procedures, bibliographical research was used, primary and secondary source documents. According to the data collected, education was seen as the primordial basis for the academic/professional evolution of an individual, whose continuous training directly influences the qualification of the workforce, which, in turn, benefits economic growth. It was also verified that the performance of the IFS-Itabaiana in the dimensions of teaching, research and extension is directly linked to the local economic potential, which makes it possible to state that the IFS contributes to the development of Itabaiana, even with incipient results.